PERLINDUNGAN HUKUM BAGI SUAMI ISTERI DALAM PELAKSANAAN PERJANJIAN PERKAWINAN MENURUT HUKUM ISLAM - Indira Hastuti (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The marriage covenant could function as preparation for entering the household ark. In Indonesia, which still upholds eastern customs, the community considers this agreement to be an unusual sensitive issue. Islamic law does not specifically regulate marriage agreements. Based on the discussion, it can be concluded that legal protection for husband and wife in implementing a marriage agreement according to Islamic law is regulated in Chapter VII Articles 45 and 47 KHI. Husband and wife can make a marriage agreement during the marriage whose purpose is to protect the legal interests of the husband or wife against the property they own or will have.